An Innovative Elastoplastic Analysis for Soft Surrounding Rock considering Supporting Opportunity Based on Drucker-Prager Strength Criterion. (25th March 2021) - Wang, Rui; Liu, Xu-dong; Bai, Jian-biao; Yan, Shuai; Xu, Jun
Abstract : In order to study the mechanism of excavation and supporting process of equivalent circular roadway, the model of soft roadway was established firstly. The elastoplastic solutions in excavation process were deduced based on Drucker-Prager strength criterion. Then, the elastoplastic solution under supporting condition was obtained based on homogenization method under the condition of rockbolts and liner supporting. Lastly, an example was analyzed to study the effect of different factors such as "space effect, " supporting opportunity, stresses, surrounding displacement, and the radius of plastic zone. Based on theoretical research case, the change rules of considering the "space effect" and the supporting opportunity when calculating the subarea of the roadway were discussed, the control of interval distance of rockbolts on the displacement of surrounding rock mainly reflecting in the plastic residual zone and the "space effect" in excavation, and the supporting time to control the displacement of surrounding rock not being ignored are revealed. The results can provide an important theoretical basis for the stability evaluation and quantitative support design of roadway surrounding rock. Therefore, the "space effect" and the supporting time to control the displacement and stresses of surrounding rock can not being ignored in underground engineering.